The impact of the coronavirus disease 2019 pandemic on the utilisation of emergency urological services - Madanelo, Mariana (BJU Int, 2020)
OBJECTIVES: To compare the number of patients attending the Urology Emergency Department (ED) of the Centro Hospitalar Universitário do Porto (CHUP), as well as their demographic characteristics, the reasons for admission, the clinical severity under the Manchester triage system (MTS), and the need for emergency surgery or hospitalisation, during the coronavirus disease 2019 (COVID‐19) pandemic and the equivalent period in 2019. PATIENTS AND METHODS: Data were collected from patients attending the Urology ED of the CHUP over 3 weeks, from 11 March to 1 April 2020, and from the same period in the previous year (from 11 March to 1 April 2019). RESULTS: During the pandemic, 46.4% fewer patients visited our urological ED (122 vs 263). There was no significant difference in the mean age or the number of old patients (aged ≥65 years) between the two periods. However, significantly fewer female patients sought emergency urological services during the COVID‐19 pandemic period (32.7% vs 14.8%, P < 0.05). No significant differences were noted between different clinical severity groups under the MTS. In 2019, significantly less patients required hospitalisation. The most common reasons for admission, during both periods, were haematuria, renal colic and urinary tract infections. The authors recognise that the study has several limitations, namely, those inherent to its retrospective nature. CONCLUSION: COVID‐19 significantly influenced people’s urological care‐seeking behaviour. Understanding the present situation is helpful for predicting future urological needs. Based on the results of this study, we have reason to speculate that people’s requirements for urological services might grow explosively in the post‐COVID‐19 period. There should be further studies about the real state of long‐term urological services and the consequences that this pandemic may have in terms of morbimortality not directly related to the severe acute respiratory syndrome coronavirus 2.